Cardiac substructure dosimetry in postoperative breast-conserving radiotherapy: a novel 8-field IMRT approach for internal mammary node irradiation using MONACO - Xie, Ziyi; Hao, Shuai; Wu, Xiao; Liu, Yinliang; Bao, Chaoen; Zhao, Ruhan; Liu, Ming; Cao, Xiaohui (Frontiers in Oncology, 2026)
ObjectiveTo evaluate the dosimetric impact of internal mammary lymph node (IMN) inclusion versus exclusion (non-IMN) on cardiac substructures in postoperative breast-conserving radiotherapy, providing evidence-based insights for clinical decision-making.MethodsThis study included 20 breast cancer patients (10 on the left and 10 on the right) who had previously received radiotherapy in our hospital after breast conserving surgery. The clinical target volume (CTV) encompassed the ipsilateral breast, supraclavicular lymph nodes, and internal mammary lymph nodes (IMNs). Organs at risk (OARs) comprised the heart and its substructures—including the left ventricle (LV), left atrium (LA), right ventricle (RV), right atrium (RA), anterior myocardial territory (AMT), left anterior descending artery (LAD), left circumflex artery, and right coronary artery—as well as bilateral lungs, ipsilateral/contralateral lungs, contralateral breast, thyroid, and spinal cord. For both target delineation strategies, treatment planning utilized 8-field fixed-beam intensity-modulated radiation therapy (IMRT) with 6 MV X-rays, delivering 50 Gy in 25 fractions over 5 weeks to 95% of the planning target volume (PTV). Continuous variables were reported as mean ± standard deviation (SD). Normality was assessed using Shapiro-Wilk tests, with paired t-tests applied for normally distributed data and Wilcoxon signed-rank tests for non-parametric comparisons. Statistical significance was defined as P<0.05 (two-tailed).ResultsComparative dosimetric analysis revealed significantly improved planning target volume homogeneity index (HI) and conformity index (CI) in the non-IMN treatment irradiation cohort compared to the IMN group for both left- and right-sided breast cancers (P< 0.05). Subgroup analysis: Left-sided breast cancer analysis: The IMN-irradiated cohort demonstrated significantly elevated cardiac dose parameters, with increased Dmax (P<0.05) and Dmean (P<0.05) for the whole heart compared to non-IMN treatment. Paradoxically, the left ventricle exhibited reduced mean dose (707.61 ± 141.28 cGy vs. 825.94 ± 141.46 cGy, P<0.05) in the IMN group. Significant dose escalation was observed in the right cardiac structures, including right ventricle Dmax/Dmean, right atrium Dmean, anterior myocardial territory Dmax, and right coronary artery Dmax/Dmean (P<0.05). However, no statistically significant differences were detected in heart volumetric parameters (V5, V10, V40), left ventricle Dmax, left atrial doses (Dmax/Dmean), right atrium Dmax, anterior myocardial territory Dmean, or coronary artery doses (LAD and left circumflex Dmax/Dmean). For right-sided breast cancer cases, comparative dosimetric analysis revealed distinct patterns in cardiac substructure exposure: Cardiac dose parameters: No statistically significant differences were observed in mean heart dose (Dmean) or low-dose exposure (V5) between the treatment groups. Atrial exposure: The IMN-irradiated cohort demonstrated significantly elevated maximum dose (Dmax) to the right atrium (P< 0.05). Myocardial territory: The IMN group showed increased maximum dose (P< 0.05) and significantly higher V10 (P<0.05) to the anterior myocardial territory. Coronary arteries: A paradoxical reduction in left circumflex artery Dmax was observed in the IMN-treated patients (P<0.05). Non-significant parameters: Anterior myocardial territory Dmean, left circumflex artery Dmean, LAD (both Dmax/Dmean), and right coronary artery (both Dmax/Dmean) showed comparable dose distributions between groups.Conclusion1. The dosimetric analysis reveals that 8-field intensity-modulated radiation therapy (IMRT) with internal mammary node (IMN) irradiation significantly increases mean heart dose and critical cardiac substructure exposure in left-sided breast cancer (P<0.05), potentially elevating long-term cardiovascular toxicity risks. However, right-sided treatments demonstrated no significant differences in mean heart dose (P>0.05) or left anterior descending artery (LAD) dose exposure. These findings suggest that clinical decision-making should carefully weigh the competing risks of locoregional recurrence against potential cardiotoxicity, with consideration given to advanced radiotherapy techniques for cardiac dose optimization when treating left-sided malignancies. 2. Current evaluation metrics for breast cancer radiotherapy planning, predominantly focused on mean heart dose and low-dose volume parameters, may not sufficiently capture the risk of radiation-induced cardiac toxicity. Comprehensive dosimetric assessment requires delineation of cardiac substructures (e.g., ventricles, coronary arteries) as discrete organs-at-risk (OARs), with their dose constraints systematically integrated into plan optimization and quality assurance protocols. This paradigm shift toward substructure-sparing approaches could enhance the therapeutic ratio by minimizing late cardiovascular complications while maintaining target coverage. 3. Postoperative breast-conserving radiotherapy should follow guideline recommendations regarding IMN irradiation strictly.